Preventive Behaviors for Hypertension among Adults in Narathiwat Province - Tongnuang, Patcharawadee; Hajichearong, Rohana; Wayu, Wanisa; Bing, Asmanisan; Hajisaaree, Azeema; Kabae, Adianee; Chesamaae, Anis; Cheamah, Husna; Saree, Salwa; Waming, Sofiya; Kadae, Yasmee (Princess of Naradhiwas University Journal, 2019)
The purposes of this study were described the preventive behaviors for hypertension and compared the preventive behaviors for hypertension among adults in Narathiwat province, following personal characteristics. The 381 adults were stratified by random sampling in Narathiwat province. The research instrument was the preventive behaviors for hypertension questionnaire which were verified by 3 experts and the content validity index was 1.00. The Cronbach’s alpha of reliability was 0.81. Data were analyzed by using descriptive statistics, t-test, and one-way anova. The findings revealed that the total score of the preventive behaviors for hypertension were moderate level. Considering in each aspect, the score of DASH diet, less sodium consumption, exercise and physical activity, risk avoidance, and weight control had moderate level. Meanwhile, stress management was high level. Moreover, adult who varied in gender, age and education had a different level of hypertension preventive behaviors significantly.